PUNISHMENT AS A FACTOR OF HEROIC TRANSFORMATION IN ARCHNARRATIVES - Danišová, Nikola (Porównania, 2019)
The given study focuses on fundamental thematic transformation patterns of human protagonists in the fictive world of ancient narratives (fairy tales, myths, eposes, legends, etc.) from many world cultures (from Europe, Asia, America, Africa, Australia). Our aim will be to find out in what narrative situations and sujet-motif constellations a heroic transformation becomes a punishment. The intent of the proposed research is not only to contribute to the basic typological classification of the transformations of the characters in the investigated magic narratives, but also to conceptually affect the archetypal meaning of the essential transformation for punishment.